Diversity of Antimicrobial Resistance Phenotypes in Salmonella Isolated from Commercial Poultry Farms - Liljebjelke, Karen A.; Hofacre, Charles L.; White, David G.; Ayers, Sherry; Lee, Margie D.; Maurer, John J. (Frontiers in Veterinary Science, 2017)
Salmonella remains the leading cause of foodborne illness in the United States, and the dissemination of drug-resistant Salmonellae through the food chain has important implications for treatment failure of salmonellosis. We investigated the ecology of Salmonella in integrated broiler production in order to understand the flow of antibiotic susceptible and resistant strains within this system. Data were analyzed from a retrospective study focused on antimicrobial resistant Salmonella recovered from commercial broiler chicken farms conducted during the initial years of the US FDA’s foray into retail meat surveillance by the National Antimicrobial Resistance Monitoring System (NARMS). Sixty-three percentage of Salmonella were pan-susceptible to a panel of 19 antimicrobials used by the NARMS program. Twenty-five antimicrobial resistance phenotypes were observed in Salmonella isolated from two broiler chicken farms. However, Salmonella displaying resistance to streptomycin, alone, and in combination with other antibiotics was the most prevalent (36.3%) antimicrobial resistance phenotype observed. Resistance to streptomycin and sulfadimethoxine appeared to be linked to the transposon, Tn21. Combinations of resistance against streptomycin, gentamicin, sulfadimethoxine, trimethoprim, and tetracycline were observed for a variety of Salmonella enterica serovars and genetic types as defined by pulsed-field gel electrophoresis. There were within and between farm differences in the antibiotic susceptibilities of Salmonella and some of these differences were linked to specific serovars. However, farm differences were not linked to antibiotic usage. Analysis of the temporal and spatial distribution of the endemic Salmonella serovars on these farms suggests that preventing vertical transmission of antibiotic-resistant Salmonella would reduce carcass contamination with antibiotic-resistant Salmonella and subsequently human risk exposure.